2012
DOI: 10.1021/jp211539z
|View full text |Cite
|
Sign up to set email alerts
|

First-Principle Study on High-Pressure Behavior of Crystalline Polyazido-1,3,5-triazine

Abstract: A detailed study on the structural, electronic, and thermodynamic properties of the solid polyazide 4,4′,6,6′-tetra(azido)azo-1,3,5-triazine (TAAT) under the hydrostatic pressure of 0−100 GPa was performed using the plane-wave density function theory method. The predicted crystal structure compares well with the experimental results at the ambient pressure. The results show that a pressure less than 40 GPa does not significantly change the crystal and molecular structures. When the higher pressure is applied, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 49 publications
3
15
0
Order By: Relevance
“…It has been found that TAHT has better thermal stability than its analogue TAAT, which is in agreement with the experimental results [26,27]. Further theoretical investigations have been carried out for both TAHT and TAAT in terms of their geometric and electronic parameters by considering the effect of the crystalline field [28,29]. Another compound which contains 4,6-diazido-1,3,5-triazineyl group is 4,6-diazido-N-(2,4,6-trinitrophenyl)-1,3,5-triazin-2-amine (TANDAzT).…”
Section: Introductionsupporting
confidence: 81%
“…It has been found that TAHT has better thermal stability than its analogue TAAT, which is in agreement with the experimental results [26,27]. Further theoretical investigations have been carried out for both TAHT and TAAT in terms of their geometric and electronic parameters by considering the effect of the crystalline field [28,29]. Another compound which contains 4,6-diazido-1,3,5-triazineyl group is 4,6-diazido-N-(2,4,6-trinitrophenyl)-1,3,5-triazin-2-amine (TANDAzT).…”
Section: Introductionsupporting
confidence: 81%
“…It has been found that TAHT has better thermal stability than its analogue TAAT, which is in agreement with the experiments [19][20][21] . Further theoretical investigations have been carried out for both TAHT and TAAT in terms of their geometric and electronic parameters by considering the effect of the crystalline field 22,23 . TAHT has theoretical heat of sublimation of 38.68 kcal mol -1 , while its detonation velocity and detonation pressure in solid state are predicted to be 7.44 km s -1 and 23.71 GPa,…”
Section: Introductionmentioning
confidence: 99%
“…Plainly, the latter is simpler and instructive. In fact, it has been widely used in the field of energetic materials …”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, our group has done lots of studies about high energetic materials on various properties . Among them, a nitro cage compound, namely 4‐trinitroethyl‐2, 6, 8, 10, 12‐pentanitrohexaazaisowurtzitane (TNE‐CL‐20) (in Figure ) prepared in recent years (in Figure ), was researched on its structural and energetic properties in gas phase .…”
Section: Introductionmentioning
confidence: 99%